Temperature dependences of piezoelectric and linear electrooptic properties of rhombohedral 0.67.Pb(Mg1/3Nb2/3)O-3-0.33PbTiO(3) single crystal oriented in (111) direction - Song, Hyun-Cheol; Ha, Jong-Yoon; Kim, Jin-Sang; Yoon, Seok-Jin; Jeong, Dae-Yong (INST PURE APPLIED PHYSICS, 2007)
We characterized the temperature dependences of the linear electrooptical (E-O) and piezoelectric coefficients of the rhombohedral 0.67Pb(Mg1/3Nb2/3)O-3-0.33PbTiO(3) single crystals oriented along the (111) direction (the spontaneous polarization direction). The E-O coefficients of the 0.67PMN-0.33PT single crystals were r(333) = 107 pm/V at room temperature and 950 pm/V at 80 degrees C. The piezoelectric coefficient d(311) of the 0.67PMN-0.33PT single crystals increased from 45 pC/N at room temperature to 1015 pC/N at 80 degrees C. Large E-O and piezoelectric coefficients at 80 degrees C were from the engineering domain configuration induced by a transition from the rhombohedral phase othorhombic phase.
Keywords: OXYGEN-OCTAHEDRA FERROELECTRICS